From Human-Systems Integration to Human-Systems Inclusion for use-centred inclusive manufacturing control systems. Issue 1 (2021) - Vanderhaegen, F.; Nelson, J.; Wolff, M.; Mollard, R.
Abstract: The paper discusses about human-systems inclusion as a new way to take into account human factors on systems engineering. This process applies not only principles from human-supported by automation but also those on automation-supported by human to improve autonomy between humans and machines and autonomy between people. The main concern of human-systems integration is the consideration of a low number of future users in the design process or of the feedback of a majority of users in the evaluation process. Human-system inclusion considers that the system has to take into account and adapt to all users whatever their social, economic, physical or cognitive state, or disability. The concept of "human in the loop" or of "human touch" is usually limited to the definition of the role of humans and machines. It does not consider dynamic variability of users and systems abilities, and anticipate the feasible development of autonomous machines by reducing progressively human engagement in the control and supervisory loop. The paper presents both integration and inclusion concepts for Industry 4.0, and then suggests some challenging perspectives for use-centred inclusive manufacturing control systems in terms of opportunities and threats.